Congenital neck fistulas and cysts in adults - Estrugo, Roberto L.; Laviña, Raúl (Cirugía del Uruguay, 1982)
A serie of 18 cases of cysts and fistulas derived of the thyroglossal tract, tha branchial archs and other embriologycal structures. The finding of two congenital cysts in 320 pieces of thyroidectomy is remarked. In positive diagnosis of neck tumors, its importan t a correct c!inic history, as it is the value of citologic punction, fistulography and non invasive diagnosis procedures. Origin and frecuency ·of malignant transformation are discussed. High average of re currencies is result of inadequate treatment. According with our little serie and the consulted bibliography, we recommend radical treatment sistematically.